2020
DOI: 10.1371/journal.pone.0236702
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of balancing behaviour during continuous perturbations of stance. Supra-postural visual tasks and platform translation frequency modulate adaptation rate

Abstract: When humans are administered continuous and predictable perturbations of stance, an adaptation period precedes the steady state of balancing behaviour. Little information is available on the modulation of adaptation by vision and perturbation frequency. Moreover, performance of supra-postural tasks may modulate adaptation in as yet unidentified ways. Our purpose was to identify differences in adaptation associated to distinct visual tasks and perturbation frequencies. Twenty non-disabled adult volunteers stood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 143 publications
1
3
0
Order By: Relevance
“…Haptic information helps an individual develop strategies to achieve a task successfully, but requires voluntary decisions about and, often, awareness of the task's state of continuous change (i.e., supra-postural mechanism). [21][22][23] Our results support previous findings related to haptic contact during walking and standing tasks that employed dogs. 16,18 The interdependence between sources of constraints (e.g., blindly handling the leash and the motion of the dog's neck and body during locomotion) expands the biological boundaries of information pickup and reorganizes both organisms' configurations-human's and dog's-via their haptic systems to support behavioral tasks (e.g., standing still).…”
Section: The Moving Dog Conveys Haptic Information For Postural Controlsupporting
confidence: 89%
“…Haptic information helps an individual develop strategies to achieve a task successfully, but requires voluntary decisions about and, often, awareness of the task's state of continuous change (i.e., supra-postural mechanism). [21][22][23] Our results support previous findings related to haptic contact during walking and standing tasks that employed dogs. 16,18 The interdependence between sources of constraints (e.g., blindly handling the leash and the motion of the dog's neck and body during locomotion) expands the biological boundaries of information pickup and reorganizes both organisms' configurations-human's and dog's-via their haptic systems to support behavioral tasks (e.g., standing still).…”
Section: The Moving Dog Conveys Haptic Information For Postural Controlsupporting
confidence: 89%
“…Centre of feet pressure (CoP) path length and sway area, median spectrum frequency, the mean level of the full spectrum (from 0.01 to 2 Hz) and of the distinct frequency windows were used to assess the time course of the changes in these variables over the eight consecutive repetitions. We postulated that an exponential model would fit the trends, as described on several other occasions (Tjernström et al, 2010;Schmid et al, 2011;Welch and Ting, 2014;Patel and Bhatt, 2015;Sozzi et al, 2020). To compare these trends across conditions, all data were logtransformed, and regression lines fitted to these data, even if for certain participants, sensory conditions, metrics, and frequency windows an exponential trend was not obvious.…”
Section: Data Treatment and Statisticsmentioning
confidence: 99%
“…The responses to a consecutive set of perturbation trials become usually smaller than those to the initial trials. Perturbations of balance can have various configurations, like translations or tilts of the base of support (Gollhofer et al, 1989;Corna et al, 1999;Schmid et al, 2011;Welch and Ting, 2014;Sozzi et al, 2020) or sudden changes in the velocity of the treadmill upon which subjects walk (Patel and Bhatt, 2015;McCrum et al, 2017) or else strikes of a loaded pendulum hitting the upper body of a standing person (Kaewmanee et al, 2020). Also, translational visual stimuli challenge the sensory reweighting mechanisms (Isableu et al, 2011;Fransson et al, 2019), much as occurs for vestibular stimulation (St George and Fitzpatrick, 2011;Barmack and Pettorossi, 2021) or muscle vibration (Bove et al, 2006;Duysens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The data have been collected here and analysed on the basis of one single trial per subject per condition (i.e., the first trial of a series of eight trials), administered in order to investigate the effect of the sensory conditions in the adaptation to repeated stance performances. Given the inter-individual variability in the stance performance (9,176), particularly when standing on foam, this procedure is certainly a limitation however hardly avoidable because repetition of stance trials produces significant adaptation in the balancing pattern (8,127,(177)(178)(179)(180). Alsubaie et al (181) have recently shown that different measures of postural sway are reliable when recorded at two visits 1 week apart, including measures with unstable BoS and sensory conditions.…”
Section: Limitationsmentioning
confidence: 99%